ExLing 2018: Proceedings of 9th Tutorial and Research Workshop on Experimental Linguistics 2019
DOI: 10.36505/exling-2018/09/0028/000361
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the phonetic expression of successful motivation

Abstract: The present study provides a comprehensive acoustic phonetic analysis of motivational speech by collecting, annotating and processing 50 minutes of speech data representing less and more successful degrees of motivation. The analysis shows significant differences regarding the acoustic phonetic features f 0 (median, range, variation), intensity (median, range) and speaking rate. We observe inconsistent results for the variation of intensity, pointing to the necessity of a more fine-grained analysis of this fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…While many speakers may be considerate of the words they use to stimulate others to act, they might underestimate the effect of tone of voice, and this oversight is echoed by a research body that has largely focused on listeners' reactions to semantics rather than prosody in controlling versus autonomy-supportive motivational speech (see Voße & Wagner, 2018;Weinstein et al, 2018 for exceptions). One meaningful way to explore listener reactions to these motivational styles of communicating is in terms of listeners' defiancetheir tense desire to do the opposite of what is askedsince defiance represents a motivationallyrelevant psychological experience that has been previously shown to have meaningful behavioral correlates Pavey & Sparks, 2009;Van Petegem et al, 2015, 2015aWeinstein & Przybylski, 2018).…”
Section: Present Researchmentioning
confidence: 99%
“…While many speakers may be considerate of the words they use to stimulate others to act, they might underestimate the effect of tone of voice, and this oversight is echoed by a research body that has largely focused on listeners' reactions to semantics rather than prosody in controlling versus autonomy-supportive motivational speech (see Voße & Wagner, 2018;Weinstein et al, 2018 for exceptions). One meaningful way to explore listener reactions to these motivational styles of communicating is in terms of listeners' defiancetheir tense desire to do the opposite of what is askedsince defiance represents a motivationallyrelevant psychological experience that has been previously shown to have meaningful behavioral correlates Pavey & Sparks, 2009;Van Petegem et al, 2015, 2015aWeinstein & Przybylski, 2018).…”
Section: Present Researchmentioning
confidence: 99%
“…In this work, we focus on motivation in the context of sports and healthy nutrition and define the term motivation as a process which results in a readiness to act within an individual (Mook, 1987, cited in Rudolph, 2013. This process is complex and can be influenced by several factors, among which are leadership communication (Mayfield and Mayfield, 2018) and phonetics (Voße and Wagner, 2018). It has been discussed and partially shown that specific patterns on the level of language and speech influence the motivating impact of a person positively, while other patterns are assumed to be detrimental in the context of motivation.…”
Section: Introductionmentioning
confidence: 99%
“…MM, E, and DG are claimed to be essential and, therefore, should all occur in motivating language. Voße and Wagner (2018) focus on the acoustic-phonetic expression of motivation. Their hypotheses are inspired by recent studies on emotional speech and charismatic speech.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations